Ticket to Higher Education: A Decision-Making Tool for Choosing Higher Education Offerings in South Africa - Sesale, Eunice (Universitas Nahdlatul Ulama Surabaya, 2025)
Despite sustained policy interventions aimed at expanding access to higher education, significant disparities persist, particularly for marginalized students from historically disadvantaged communities. Additionally, while the overall enrollment figures have significantly improved, systemic inequities continue to hinder equitable participation. This paper critically examines key access barriers, such as financial insecurity, academic under-preparedness, ambiguity surrounding admission criteria, and administrative delays such as late document submission. The paper proposes a data-informed decision-making framework tailored to support prospective students, especially first-generation applicants in navigating the complex pathways of university, Technical and Vocational Education and Training college, and matric re-write applications. The framework leverages robust academic performance indicators to recommend optimal educational trajectories and integrates real-time guidance on funding opportunities. By streamlining procedural workflows and enhancing access to accurate, timely information, the tool seeks to empower students to make informed academic decisions. The framework further offers scalable, practical intervention to mitigate both institutional and socioeconomic barriers, contributing to a more inclusive and equitable access to higher education institutions in South Africa.